In vitro anti-inflammatory and anticoagulant activities of alkaloïds extracted from nopals of inermis Algerian Opuntia ficus indica (L). - Moussaoui, Badreddine; Hanafi, Tahar; Rahali, Abdallah; Guemou, Laid; Reghioui, Bachir; Zemour, Kamal; Riazi, Ali (Journal of Agriculture and Applied Biology, 2024)
The dearth of information surrounding the utilization of Opuntia cladode alkaloids underscores a critical gap in understanding their pharmacological properties and therapeutic potential, emphasizing the need for further comprehensive investigations. The present study aims to investigate the in vitro anti-inflammatory, anticoagulant, and antimicrobial activities of alkaloïds belonging to young cladodes (nopals) of inermis Algerian Opuntia ficus indica. The assessed alkaloïds showed a moderate anti-inflammatory effect regarding the BSA protein protection with a maximum of 51.04±1.84 % compared to 84.22±2.38 % for Diclofenac sodium as a positive standard. However, their stabilization of red blood cells membrane against induced hemolysis was greater than Diclofenac (52.38±2.01 % vs 48.97±2.73 %). The two assays had a significant correlation (< 0.05) of 0,968. Nopal alkaloïds extended the coagulation time (1.24 fold) by significantly affecting the exogenous pathway PT only, whilst they were ineffective against the endogenous pathway APTT. Conversely, Algerian nopal alkaloïds had neither bacteriostatic nor bactericide influence at 2 mg ml-1 on Candida albicans yeast or the six tested pathogenic bacterial strains. In perspective, the purification of these Opuntia nopal alkaloïds and understanding their accurate mechanism of action are clearly the strategic steps to illustrate their overall curative potential.